2014
DOI: 10.1002/bmc.3348
|View full text |Cite
|
Sign up to set email alerts
|

A validated LC‐MS/MS assay for simultaneous quantification of methotrexate and tofacitinib in rat plasma: application to a pharmacokinetic study

Abstract: A highly sensitive, specific and rapid LC-ESI-MS/MS method has been developed and validated for simultaneous quantification of methotrexate (MTX) and tofacitinib (TFB) in rat plasma (50 μL) using phenacetin as an internal standard (IS), as per the US Food and Drug Administration guidelines. After a solid-phase extraction procedure, the separation of the analytes and IS was performed on a Chromolith RP₁₈e column using an isocratic mobile phase of 5 m m ammonium acetate (pH 5.0) and acetonitrile at a ratio of 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 18 publications
(24 reference statements)
1
31
0
Order By: Relevance
“…For the extraction of TOF from various biological matrices all three conventional procedures were employed namely, protein precipitation (PPT) (Paniagua et al, ), liquid–liquid extraction (LLE) (Abdelhameed et al, ; Kadi et al, ; Kumar et al, ) and solid‐phase extraction (Dowty et al, ; Krishnaswami, Wang, et al, ; Krishnaswami, Boy, et al, ; Menon et al, ; Sharma et al, ). Initially, PPT was tried with acetonitrile and methanol in the presence of a base.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the extraction of TOF from various biological matrices all three conventional procedures were employed namely, protein precipitation (PPT) (Paniagua et al, ), liquid–liquid extraction (LLE) (Abdelhameed et al, ; Kadi et al, ; Kumar et al, ) and solid‐phase extraction (Dowty et al, ; Krishnaswami, Wang, et al, ; Krishnaswami, Boy, et al, ; Menon et al, ; Sharma et al, ). Initially, PPT was tried with acetonitrile and methanol in the presence of a base.…”
Section: Resultsmentioning
confidence: 99%
“…To obtain better selectivity and sensitivity as well as shorter analysis time, appropriate selection of chromatographic conditions like mobile phase and its pH, column and flow rate was essential. In the majority of the methods (Abdelhameed et al, ; Dowty et al, ; Kadi et al, ; Kumar et al, ; Paniagua et al, ; Sharma et al, ) the analysis time was ≥4 min. Initially, some reversed‐phase columns like Gemini C 18 (150 × 4.6 mm, 5.0 μm), Cosmosil C 18 (100 × 4.6 mm, 5.0 μm) and Symmetry C 18 (100 × 4.6 mm, 5.0 μm) were tested using formic acid–ammonium formate, acetic acid–ammonium acetate buffer and methanol–acetonitrile in different ratios.…”
Section: Resultsmentioning
confidence: 99%
“…conversion of n = 3 glutamate linkage to n = glutamate linkage) owing to freeze–thaw cycles. In the post‐column irradiation method to convert methotrexate to its irradiated analog that promotes fluorescing properties, it may be important to ascertain several key parameters. Amongst the parameters: (a) the concentration of the oxidizing agents used, such as hydrogen peroxide and potassium permanganate, needs to be carefully selected; (b) the time duration of the irradiation has to be critically evaluated; and (c) the length of the capillary coil where irradiation occurs need to be optimized. Selectivity considerations need to be highlighted, especially those obtained from extraneous endogenous peaks in individual patients that may interfere in the analysis of various polyglutamates and, therefore, the chromatographic data need to closely scrutinized for any aberrations owing to matrix‐related endogenous interference at the peaks of interest; To the best of our knowledge incurred sample re‐analysis (ISR) has not been reported in the human assays in reviewed published methods for methotrexate but was reported in a preclinical study in rat plasma (Sharma et al, ). Because ISR requirement is imperative for bioanalytical data in the present regulatory climate (Fluhler et al, ; Srinivas, ; Yadav & Shrivastav, ), it may be prudent to evaluate ISR for methotrexate and if possible for its key metabolites in human assays.…”
Section: Discussionmentioning
confidence: 99%
“…Sharma et al () have reported a simple LC–MS/MS for the simultaneous quantitation of methotrexate and tofacetanib, a recently approved drug to treat RA (Fleischmann et al, ). One of the key issue identified in the assay development was with respect to difficulty in using a liquid–liquid extraction procedure for recovering methotrexate and tofacetanib from plasma because of differences in the log P values for both analytes (methotrexate −1.80 and tofacetanib 1.80).…”
Section: Case Studiesmentioning
confidence: 99%
“…Other than HPLC, various other methods have also been reported such as LC-MS/MS (Al-Ghobashy et al, 2016), LC-ESI-MS/MS (Sharma et al, 2014), electrochemistry (Li et al, 2007;Saleh, Alkal, Refaat, & Abdel-aal, 2016) and fluorescence polarization immunoassay (Ozkan, Ozcan, & Alparslan, 2011), for simultaneous estimation of MTX with other drugs in pharmaceutical and biological samples. Similarly, different methods including RP-HPLC (Mehta, Prajapat, & Gohil, 2017), LC-UV and LC-MS (Guo et al, 2007) and LC-ESIMS (Parekh, Vaghela, Sutariya, & Sanyal, 2010) have also been reported for analysis of TEF in pharmaceutical and biological samples.…”
Section: Introductionmentioning
confidence: 99%